Nursing Implementation Of Distraction Techniques: Play Therapy (Doll) With Anxiety Problems In Thalasemia Children - Syeftiana; Yunike; Jawiah (International Journal Scientific and Professional, 2022)
Thalassemia is a disease that is passed from parents to their children in the womb which results in sufferers having to undergo regular blood transfusions to increase hemoglobin levels in the blood. Routine transfusions can cause psychological impacts such as anxiety in children. Playing is an effective way to reduce anxiety in children and can be a diversion or relaxation. The aim of the case study is that researchers are able to carry out nursing implementation of distraction techniques: play therapy (dolls) with anxiety problems in thalassemia children. Method: This research design uses descriptive methods in the form of a case study. Two respondents took cases, namely thalassemia patients with anxiety in the Talang Betutu Community Health Center area and the Sei Selincah Community Health Center area. Results: The implementation of nursing provided in the form of doll play therapy was effective in reducing anxiety in children. Anxiety scores decreased after doll play therapy. Conclusion: Nursing implementation of distraction techniques: play therapy (dolls) is effective in reducing anxiety in thalassemia children